2014
DOI: 10.1186/s12888-014-0249-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported contacts for mental health problems by rural residents: predicted service needs, facilitators and barriers

Abstract: BackgroundRural and remote Australians face a range of barriers to mental health care, potentially limiting the extent to which current services and support networks may provide assistance. This paper examines self-reported mental health problems and contacts during the last 12 months, and explores cross-sectional associations between potential facilitators/barriers and professional and non-professional help-seeking, while taking into account expected associations with socio-demographic and health-related fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 45 publications
2
37
0
1
Order By: Relevance
“…Practical factors associated with accessing treatment, including cost, transportation, and lack of time emerged as an important barrier towards help‐seeking. Previous studies on help‐seeking for mental health problems have reported similar findings, particularly in rural areas and among people from potentially disadvantaged groups . Although the included studies in the present review did not focus on rural areas, these practical barriers were similarly important, especially among ethnically diverse samples.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Practical factors associated with accessing treatment, including cost, transportation, and lack of time emerged as an important barrier towards help‐seeking. Previous studies on help‐seeking for mental health problems have reported similar findings, particularly in rural areas and among people from potentially disadvantaged groups . Although the included studies in the present review did not focus on rural areas, these practical barriers were similarly important, especially among ethnically diverse samples.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies on helpseeking for mental health problems have reported similar findings, particularly in rural areas and among people from potentially disadvantaged groups. 29,32,53 Although the included studies in the present review did not focus on rural areas, these practical barriers were similarly important, especially among ethnically diverse samples. In particular, financial difficulties were endorsed as a barrier by a majority of women with eating disorders from ethnically diverse backgrounds 24 ; however, no difference in treatment seeking between women of different ethnicities was found.…”
Section: Prominent Barrier Themesmentioning
confidence: 99%
“…We did not identify sex differences in PDS and CDS, but differences in the manner in which men and women seek help, discuss and understand problems, and engage in support networks and services should nonetheless be considered by initiatives for relieving drought-related stress. 5 Programs of support for drought-affected communities should incorporate an understanding of the relationship between drought and mental health, and take factors into account that influence PDS and CDS.…”
Section: Resultsmentioning
confidence: 99%
“…The biophysical impacts of drought are intertwined with social and structural factors, exposing different social and demographic groups in diverse geographic locations to a variety of risks and sensitivities 2 . Australian rural communities are vulnerable to the socio‐economic impacts of drought because they rely on primary production and water‐intensive industries, 3 , 4 as well as to the health effects associated with difficulties in accessing health care 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation